1989
DOI: 10.1021/jm00129a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hypolipidemic and antidiabetogenic activities of .beta.,.beta.,.beta.',.beta.'-tetrasubstituted, long-chain dioic acids

Abstract: beta,beta,beta',beta'-Tetrasubstituted, long-chain dioic acids of the general formula HOOC-C(XY)-C(R2)-Q-C-(R2)-C(XY)-COOH have been synthesized and evaluated as hypotriglyceridemic-hypocholesterolemic agents in rats and as antidiabetogenic agents in ob/ob diabetic mice. The free carboxyl function of analogues of the series was mandatory for their hypolipidemic-antidiabetogenic effect while nonhydrolyzable diesters were inactive. Other structure-activity relationships were determined as a function of the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 2 publications
0
54
0
Order By: Relevance
“…Treatment with MEDICA 16. MEDICA 16 (␤,␤Ј-tetramethyl hexadecanedioic acid) is a long-chain fatty acyl analog developed as a hypolipidemic and antiobesityantidiabetogenic compound (30). Previous studies have demonstrated that MEDICA 16 significantly reduces intracellular TG content in gastrocnemius muscle, and this reduction is accompanied by an increase in insulin sensitivity (29).…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with MEDICA 16. MEDICA 16 (␤,␤Ј-tetramethyl hexadecanedioic acid) is a long-chain fatty acyl analog developed as a hypolipidemic and antiobesityantidiabetogenic compound (30). Previous studies have demonstrated that MEDICA 16 significantly reduces intracellular TG content in gastrocnemius muscle, and this reduction is accompanied by an increase in insulin sensitivity (29).…”
Section: Resultsmentioning
confidence: 99%
“…ACC, acetyl-CoA carboxylase; ACS, acyl-CoA synthetase; ␤ -Ox, ␤ -oxidation; CPT-1, carnitine palmitoyltransferase-1; G6Pase, glucose 6-phosphatase; HMGR, HMG-CoA reductase; PEPCK, phosphoenolpyruvate carboxykinase; TCA, tricarboxylic acid. compounds (82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92) and provide further clarity into their respective mechanisms ( 84,91,(93)(94)(95)(96)(97)(98)(99)(100).…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme A, palmitoyl-CoA, stearoyl-CoA, linoleoyl-CoA, arachidonoyl-CoA, arachidonic acid, and bezafibrate were from Sigma. Medica 16, as well as the coenzyme A thioesters of Medica 16 and bezafibrate, were chemically synthesized as described (21,22).…”
Section: Methodsmentioning
confidence: 99%